Система економічної безпеки підприємства: сутність, принципи та структура - Коптєва (Фадєєва), Ганна Миколаївна (ФОП Головко О. А., 2020)
Визначення наукового тезаурусу та класифікаційних ознак поняття "система економічної безпеки підприємства" відповідно до загальної теорії систем видається важливим науковим завданням, виконання якого дасть змогу впорядкувати належним чином компоненти цієї системи та встановити закономірності та принципи їх взаємодії. Метою статті є розвиток теорії та методології формування системи економічної безпеки в частині уточнення поняття "система економічної безпеки", відокремлення та відповідна ідентифікація основних функцій та принципів функціонування системи економічної безпеки. Запропоновано авторське визначення "система економічної безпеки підприємств" та встановлено основні елементи системи економічної безпеки підприємств, якими стали: об'єкт, суб'єкт, нормативно-правове забезпечення, функціональні складники, механізм функціонування та інструментарій (методики) оцінки стану системи. Запропоновано перелік основних принципів функціонування системи економічної безпеки, що відповідають сучасним реаліям господарської практики.

Creation of research thesaurus and classification characteristics of the concept "system of economic security of enterprise" in accordance with the general theory of systems appears to be an important research task, implementation of which allows to put in order components of this system and to reveal principles of their interaction. The need to consider a systematic approach to economic security is caused by the fact that many scientists have not developed yet a common view on many methodologically important issues, as well as definitions of basic concepts, including an economic security system. The system of economic security is specific for each enterprise, its completeness and effectiveness depend on the current state of regulatory framework, resources (financial, material and technical, informational), understanding by all employees of the importance of business security, as well as staff skills and experience. Goal: Determination of methodological concept characteristics and principles of functioning of the system of economic security of enterprise. The research works of economists formed the methodological basis of this study. To achieve the goal, the abstract-logical method was used for studying the nature of provided categories and concepts of the enterprise's economic security system and making conclusions. General theory of economic systems, which investigates their general principles and laws, is considered as the foundation of methodology in economic security. The author's definition of the concept "system of economic security of enterprises" is proposed and the main elements of this system are developed (objects, subjects, legal support, functional components, rules of functioning and methods of assessing the system status). Taking into account the specific features of the trade enterprises, a list of basic principles of the economic security system that meet the modern needs of economic practice is proposed. Further research should be directed towards the development of methodological foundations for the formation of a system for monitoring the economic security of enterprises, taking into account the specifics of their economic activities.
The system of economic security of enterprise: concept, principles and structure
Keywords: економіка; управління; класифікація принципів; господарська діяльність; economic security system; elements of economic security; principles of economic security; mechanism of economic security